The effects of Fe2O3 catalyst on the conversion of organic matter and bio-fuel production during pyrolysis of sewage sludge. Issue 4 (August 2019) - Huang, Zhihang; Qin, Linbo; Xu, Zhe; Chen, Wangsheng; Xing, Futang; Han, Jun
Abstract: In this paper, the pyrolysis treatment of sewage sludge is studied in a fixed bed reactor at temperatures range of 400–600 °C. Meanwhile, the catalytic effect of Fe2 O3 on the characteristics of the resulting gases, bio-oil and bio-char are also investigated. The experimental results indicate that the yields of gases and bio-oil respectively increase from 8.69 wt% and 32.54 wt% to 11.62 wt% and 38.74 wt%, and the char yield decreases from 58.77 wt% to 49.64 wt% during Fe-embedded sewage sludge pyrolysis when Fe2 O3 is added equal to 5% in the dried sewage sludge. Meanwhile, Fe2 O3 promotes the CO and H2 formation and inhibits the CH4 formation, while it exhibits no significantly effect on the composition of the bio-oil. Moreover, the bio-oil should be direct combustion for power generation due it contains higher oxygenated hydrocarbons. In addition, the bio-char exhibits good desulfurization activity. Highlights: The yields of gaseous and bio-oil increased while the char yield decreased due to the Fe2 O3 . The gas products mainly contained hydrogen, methane, carbon monoxide, and some fuel gas such as C2 and C3 hydrocarbons. Heavy oxygenated hydrocarbons in the bio-oil were as high as 90%. There were about 38% CaO in the bio-char, which could be reused as desulfurizing agent.